Pengaruh Lingkungan Kerja dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan (Studi Kasus Pada Koperasi Pegawai Pemerintah Kota Bandung) - Rintan Rahayu; Heri Nugraha; Mohammad Fahreza (LPPM Universitas Koperasi Indonesia, 2026)
This study aims to determine the effect of work environment and job satisfaction on employee productivity at the Bandung City Government Employees Cooperative. The background of this research is the decline in employee productivity caused by an unsupportive work environment and relatively low job satisfaction. The research method used is a descriptive and verifiable quantitative approach with data collection through questionnaires distributed to 25 cooperative employees. Data were analyzed using multiple linear regression to test the influence of independent variables on the dependent variable. The results showed that the work environment had a positive and significant effect on work productivity by 28.6%, job satisfaction had a positive effect by 31.8%, and simultaneously both variables had a contribution of 48.6% to employee productivity. The conclusion of this study shows that the better the work environment and the higher the job satisfaction, the higher the employee productivity will be.